2012
DOI: 10.5923/j.ajoc.20120202.06
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Activated Nitriles in the Synthesis of Some New Heterocyclic Compounds

Abstract: New 4-(2-cyanoacetamido)benzoic acid (1) was utilized as key intermediate for the synthesis of some new thiazole, pyrazole, oxazole, pyrimidine, 1,3-dithiolane, thiophene, coumarin, oxazine and pyridazine derivatives. Newly synthesized compounds were characterized by elemental analyses and spectral data (IR, 1 H NMR and mass spectra).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…Polarized cyanoketene N,S-acetal are versatile starting materials for the synthesis of a wide variety of fused heterocycles [39]. So, further reaction of compound 7 with phenyl isothiocyanate in DMF containing KOH followed by addition of methyl iodide to afford 2,2'-(5-methylthiazolo[2,3c] [1,2,4]triazole-3,6-dicarbonyl)bis(3-(methylthio)-3-(pheny lamino)acrylonitrile), (16).…”
Section: Resultsmentioning
confidence: 99%
“…Polarized cyanoketene N,S-acetal are versatile starting materials for the synthesis of a wide variety of fused heterocycles [39]. So, further reaction of compound 7 with phenyl isothiocyanate in DMF containing KOH followed by addition of methyl iodide to afford 2,2'-(5-methylthiazolo[2,3c] [1,2,4]triazole-3,6-dicarbonyl)bis(3-(methylthio)-3-(pheny lamino)acrylonitrile), (16).…”
Section: Resultsmentioning
confidence: 99%
“…The IR-spectra revealed a broad band in the region of 3500-3250 cm 1 υ OH and two other bands in region of 1185-1070 and 965-896 cm 1 for C-O-C ether bond of polypropoxy chain . 1 HNMR spectra showed that the propoxy groups protons appear as broad multiple signals in the range between 3.1-3.9 ppm , in addition to other signals of these compounds. A solution of the surfactant 1.0 wt , 25 mL was shaken vigorously for 10 seconds in a graduated cylinder with glass stopper at 25 .…”
Section: Preparation Of Nonionic Surfactants From the Synthesized Hetmentioning
confidence: 97%
“…In addition, the active methylene group of these compounds can take part in a variety of condensation and substitution reactions 1 . Moreover, these compounds are versatile and convenient intermediates in organic synthesis for heterocyclic nucleus and have generated a great deal of attention due to their interesting biological, therapeutic value and their pharmaceutical activities 2 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, aryl isothiocyanates are versatile reagents that have been used as synthetic intermediate to prepare biologically active heterocyclic compounds [18]. As a part of our program of developing new, simple, and efficient procedures for the synthesis of new aromatic compounds using readily available aryl isothiocyanates, we have recently affected recyclization of thiocarbamoyl into pyrazoles [19][20][21]. Furthermore, diverse chemotherapeutic activities have been ascribed to pyrazoles such as antimicrobial [22,23], antiparasitic [24], antiviral [25], and antineoplastic agents [26,27].…”
Section: Introductionmentioning
confidence: 99%